Logic as argumentation in formulation of news - Mohammed, Bahar; Dizay, Abdulwahid (Humanities Journal of University of Zakho, 2020)
Argumentation belongs to a group of human actions that seeks to bring about recipient‌s persuasion، it is a path through which the speaker aims to exert a kind of influence on others، one of the two parties in it tries to influence the opposite side to direct their actions or broadcast a belief or by saying it in the process of speech. Hence، it is the study of minds، and the best way to dialogue with and listen to it. If you arguing you prevent the recipients from thinking and then proposing an opinion to them، and supporting them with sufficient justifications to enable them to be convinced، then they also choose the basic features of a certain opinion that can be made acceptable to a specific audience، and this is what media platforms do; media does not share ready-made facts with the public as much as it shares with them convictions that sought to make them look like facts.The object reader has decided to read، so it is our duty to provide it with sufficient justifications to continue to do so، by mobilizing its human teams، electronic and logistical equipment that searches for enhancing mechanisms for influence and persuasion. If the news is based on logical inferences، it necessarily results in certainty.